CEREAL FLAKES FROM Ipomoea batatas AND Setaria italica AS EMERGENCY FOOD: CHEMICAL, MICROBIOLOGICAL, AND SENSORY PROPERTIES DURING STORAGE - Putri, Ratna Ariani Nilateja; Rahmi, Alia; Nugroho, Agung (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Â Â Â Â Emergency food supplies the daily human energy needs during emergencies. This research aimed to determine the effects of storage periode of cereal flakes made from sweet potatoes (Ipomoea batatas) and foxtail millet (Setaria italica) Â Â on the chemical, microbiological, and sensory properties. The composition of cereal flakes used was 75% of sweet potato flour and 25% of jewawut flour. Cereal flakes were tested for proximate levels (moisture, ash, protein, fat, and carbohydrate), crude fiber content, TPC, and sensory. The change observed after 40 days storage at 40â°C and RH 70% were 0.61-2.51% in moisture content, 2.29 - 1.91% in ash content, 7.44-7.19% in protein content, 18.79-18.09% in fat content, 70.88 - 70.40% in carbohydrate content, 5.28 - 4.98% in crude fiber content, and TPC 5.5x101 - 3.1x103 cfu/g. Forty days observation showed that cereal flakes remained in good quality for consumption based on SNI 01-4270-1996. The product is adequate as an alternative of emergency food.